Effects of In Utero and Lactational Exposure to New Generation Green Plasticizers on Adult Male Rats: A Comparative Study With Di(2-Ethylhexyl) Phthalate. (21st March 2018) - Albert, Océane; Nardelli, Thomas C; Lalancette, Claudia; Hales, Barbara F; Robaire, Bernard
Abstract: Di(2-ethylhexyl) phthalate (DEHP), a widely used plasticizer, is a ubiquitous environmental contaminant and may act as an endocrine disruptor. Early life exposures to DEHP may result in anti-androgenic effects, impairing the development of the male reproductive tract. However, data on the long-lasting consequences of such DEHP exposures on adult male reproductive function are still rare and discrepant. Previously, we identified 2 novel plasticizers, 1, 4-butanediol dibenzoate (BDB) and dioctyl succinate (DOS), as potential substitutes for DEHP that did not reproduce classically described endocrine disrupting phenotypes in prepubertal male offspring after maternal exposure. Here, we investigated the consequences of in utero and lactational exposure to BDB and DOS on adult male rat reproductive function in a comparative study with DEHP and a commercially available alternative plasticizer, 1, 2-cyclohexane dicarboxylic acid diisononyl ester (DINCH). Timed pregnant Sprague Dawley rats were gavaged with vehicle or a test chemical (30 or 300 mg/kg/day) from gestation day 8 to postnatal day 21. While DEHP exposure (300 mg/kg/day) significantly increased epididymal weight in the adult, exposure to DINCH, BDB, or DOS did not affect reproductive organ weights, steroid levels, or sperm quality. Using a toxicogenomic microarray approach, we found that adult testicular gene expression was affected by exposure to the higher dose of DEHP; transcripts such as Nr5a2, Ltf, or Runx2 were significantly downregulated, suggesting that DEHP was targeting estrogen signaling. Lesser effects were observed after treatment with either DINCH or BDB. DOS exposure did not produce such effects, confirming its potential as a responsible substitute for DEHP.